2014
DOI: 10.3991/ijet.v9i4.3480
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating E-Learning Systems: An Empirical Investigation on Students' Perception in Higher Education Area

Abstract: In search of better, traditional learning universities have expanded their ways to deliver knowledge and integrate cost effective e-learning systems. Universities' use of information and communication technologies has grown tremendously over the last decade. To ensure efficient use of the e-learning system, the Arab Open University (AOU) in Bahrain was the first to use e-learning system there, aimed to evaluate the good and bad practices, detect errors and determine areas for further improvements in usage. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…It cannot be denied that there is a positive relationship between the use of Smart-learning methods in the process of education and the students engagement in the attainment of learning goals ( [12], [13]. [14], [15]). The diversity of Smartlearning methods in scientific publications is presented by elearning, online learning and mobile learning.…”
Section: B the Methodological Tools Of Smart-educationmentioning
confidence: 99%
“…It cannot be denied that there is a positive relationship between the use of Smart-learning methods in the process of education and the students engagement in the attainment of learning goals ( [12], [13]. [14], [15]). The diversity of Smartlearning methods in scientific publications is presented by elearning, online learning and mobile learning.…”
Section: B the Methodological Tools Of Smart-educationmentioning
confidence: 99%
“…As development occurs, online learning in higher education rapidly increases and it is supported by the development of information and communications technology (ICT) (Allen & Seaman, 2017). Furthermore, several studies have shown the importance of ICT as supporting tools in educational systems (Abbad & Jaber, 2014). The different teaching methods in providing education and training have been immensely influenced by technological innovation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the results of studies comparing the learning models in both online versus face to face on TPD are still limited [18], causing a lack of information for practical needs and decision making [19]. Previous studies comparing online and face to face learning in TPD showed no differences in the level of satisfaction obtained during training, where the score and performance of teachers increased [10] as well as teacher beliefs and teaching skill [11] also the knowledge [56].…”
Section: 4mentioning
confidence: 99%
“…Previous studies that compared online versus traditional learning in higher education institutions were widely practiced [17] through diverse scopes and methods. However, such research on TPD remains rare in almost all countries was also restricted [18]. Moreover, existing studies is a lack of large-scale data for use as practical information and in decision making [19].…”
Section: Introductionmentioning
confidence: 99%